Pig Farmers’ Homes Harbor More Diverse Airborne Bacterial Communities Than Pig Stables or Suburban Homes - Vestergaard, Ditte V.; Holst, Gitte J.; Basinas, Ioannis; Elholm, Grethe; Schlünssen, Vivi; Linneberg, Allan; Šantl-Temkiv, Tina; Finster, Kai; Sigsgaard, Torben; Marshall, Ian P. G. (Frontiers in Microbiology, 2018)
Airborne bacterial communities are subject to conditions ill-suited to microbial activity and growth. In spite of this, air is an important transfer medium for bacteria, with the bacteria in indoor air having potentially major consequences for the health of a building’s occupants. A major example is the decreased diversity and altered composition of indoor airborne microbial communities as a proposed explanation for the increasing prevalence of asthma and allergies worldwide. Previous research has shown that living on a farm confers protection against development of asthma and allergies, with airborne bacteria suggested as playing a role in this protective effect. However, the composition of this beneficial microbial community has still not been identified. We sampled settled airborne dust using a passive dust sampler from Danish pig stables, associated farmers’ homes, and from suburban homes (267 samples in total) and carried out quantitative PCR measurements of bacterial abundance and MiSeq sequencing of the V3-V4 region of bacterial 16S rRNA genes found in these samples. Airborne bacteria had a greater diversity and were significantly more abundant in pig stables and farmers’ homes than suburban homes (Wilcoxon rank sum test P < 0.05). Moreover, bacterial taxa previously suggested to contribute to a protective effect had significantly higher relative and absolute abundance in pig stables and farmers’ homes than in suburban homes (ALDEx2 with P < 0.05), including Firmicutes, Peptostreptococcaceae, Prevotellaceae, Lachnospiraceae, Ruminococcaceae, Ruminiclostridium, and Lactobacillus. Pig stables had significantly lower airborne bacterial diversity than farmers’ homes, and there was no discernable direct transfer of airborne bacteria from stable to home. This study identifies differences in indoor airborne bacterial communities that may be an important component of this putative protective effect, while showing that pig stables themselves do not appear to directly contribute to the airborne bacterial communities in the homes of farmers. These findings improve our understanding of the role of airborne bacteria in the increasing prevalence of asthma and allergy.